2022
DOI: 10.14814/phy2.15364
|View full text |Cite
|
Sign up to set email alerts
|

Sports activities at a young age decrease hypertension risk—The J‐Fit+ study

Abstract: This study aimed to assess (1) blood pressure between young, current athletes, and non‐athletes early in life; (2) hypertension prevalence between former athletes and the general population later in life; and (3) understand the mechanisms between exercise training and hypertension risks in the form of DNA methylation. Study 1: A total of 354 young male participants, including current athletes, underwent blood pressure assessment. Study 2: The prevalence of hypertension in 1269 male former athletes was compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…However, because the postnatal effects of fatty acids on DNAm profiles were small, additional research is needed to verify these results. Interestingly, it was reported that performing sports activities (i.e., aerobic and resistance training) at early ages may decrease the risk of suffering hypertension in later life, probably involving DNAm changes in genes influencing several pathways related to cardiovascular function such as aldosterone-regulated sodium reabsorption, inflammatory mediator regulation of TRP channels, vascular smooth muscle contraction, cholinergic synapse, among others [30].…”
Section: Epigenetic Biomarkers Of Blood Pressure Outcomesmentioning
confidence: 99%
“…However, because the postnatal effects of fatty acids on DNAm profiles were small, additional research is needed to verify these results. Interestingly, it was reported that performing sports activities (i.e., aerobic and resistance training) at early ages may decrease the risk of suffering hypertension in later life, probably involving DNAm changes in genes influencing several pathways related to cardiovascular function such as aldosterone-regulated sodium reabsorption, inflammatory mediator regulation of TRP channels, vascular smooth muscle contraction, cholinergic synapse, among others [30].…”
Section: Epigenetic Biomarkers Of Blood Pressure Outcomesmentioning
confidence: 99%